Plant root transcriptome profiling reveals a strain-dependent response during Azospirillum-rice cooperation - Drogue, Benoît; Sanguin, Hervé; Chamam, Amel; Mozar, Michael; Llauro, Christel; Panaud, Olivier; Prigent-Combaret, Claire; Picault, Nathalie; Wisniewski-Dyé, Florence (Frontiers in Plant Science, 2014)
Cooperation involving Plant Growth-Promoting Rhizobacteria results in improvements of plant growth and health. While pathogenic and symbiotic interactions are known to induce transcriptional changes for genes related to plant defence and development, little is known about the impact of phytostimulating rhizobacteria on plant gene expression. This study aims at identifying genes significantly regulated in rice roots upon Azospirillum inoculation, considering possible favored interaction between a strain and its original host cultivar. Genome-wide analyses of Oryza sativa japonica cultivars Cigalon and Nipponbare were performed, by using microarrays, seven days post inoculation with A. lipoferum 4B (isolated from Cigalon) or Azospirillum sp. B510 (isolated from Nipponbare) and compared to the respective non-inoculated condition. A total of 7,384 genes were significantly regulated, which represent about 16 % of total rice genes. A set of 34 genes is regulated by both Azospirillum strains in both cultivars, including a gene orthologous to PR10 of Brachypodium, and these could represent plant markers of Azospirillum-rice interactions. The results highlight a strain-dependent response of rice, with 83 % of the differentially expressed genes being classified as combination-specific. Whatever the combination, most of the differentially expressed genes are involved in primary metabolism, transport, regulation of transcription and protein fate. When considering genes involved in response to stress and plant defence, it appears that strain B510, a strain displaying endophytic properties, leads to the repression of a wider set of genes than strain 4B. Individual genotypic variations could be the most important driving force of rice roots gene expression upon Azospirillum inoculation. Strain-dependent transcriptional changes observed for genes related to auxin and ethylene signalling highlight the complexity of hormone signalling networks in the Azospirillum-rice cooperation.